2016
DOI: 10.1111/pedi.12466
|View full text |Cite
|
Sign up to set email alerts
|

Home-based vs inpatient education for children newly diagnosed with type 1 diabetes

Abstract: With adequate support, children newly diagnosed with T1D can be safely managed at home following practical skills training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…However, inpatient care in pediatric diabetes varies a lot between countries. For example, outpatient/home care of newly diagnosed diabetes is common in the US or in Australia, whereas in other countries as in Japan, Sweden, Finland or Germany, children are mostly hospitalized at onset of type 1 diabetes (T1D) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, inpatient care in pediatric diabetes varies a lot between countries. For example, outpatient/home care of newly diagnosed diabetes is common in the US or in Australia, whereas in other countries as in Japan, Sweden, Finland or Germany, children are mostly hospitalized at onset of type 1 diabetes (T1D) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted with adolescents with T1DM provided diabetes education for 4 months through home and school visits and found a reduction of HbA1c levels (Oduwole et al, ). No significant difference was found between the average HbA1c scores in the studies comparing adolescents with T1DM who received home‐based care and those who received hospital‐based care after being diagnosed with T1DM (Clapin et al, ; Tiberg et al, , ). However, home care had already been provided routinely in the studies where no change was observed in HbA1c, although it has not yet been provided in Turkey.…”
Section: Discussionmentioning
confidence: 98%
“…The educational time spent with families during the first month from the child's diagnosis was similar to that reported in the RCT , both in the hospital‐based group and in the RCT‐HBHC except for the support by the diabetes nurse, with median 5.0 (min‐max 2.0–10.0) in real‐life HBHC, 7.3 (4.2–13.6) hours in the hospital‐based care and 16.5 (9.5–29.0) in the RCT‐HBHC. The support after discharge by the diabetes nurse also decreased over time; in the real‐life HBHC there was median one school visit during (min‐max 0–2) the first month from diagnosis and thereafter totally one home and school visit during the two‐year follow‐up, in the RCT there were median 2.0 (min‐max 0–7) in the control group and 3 in the RCT‐HBHC of home and school visits during the two‐year follow‐up .…”
Section: Discussionmentioning
confidence: 99%
“…The management requires a practical understanding and the development of skills for integrating the treatment in everyday life , and family functioning is closely integrated with the management of diabetes in children . A multi‐centre study evaluating hospital‐based care and home‐based care at diagnosis of type 1 diabetes is ongoing and another two randomised controlled trials (RCT) have evaluated different models of care at diagnosis , indicating that home‐based care is a safe and effective way of caring for the child and the family. However, home‐based care involves increased responsibility for the family and the growing child and could create anxiety for healthcare professionals .…”
Section: Introductionmentioning
confidence: 99%